Distinct Age-Related Epigenetic Signatures in CD4 and CD8 T Cells - Hu, Bin; Jadhav, Rohit R.; Gustafson, Claire E.; Le Saux, Sabine; Ye, Zhongde; Li, Xuanying; Tian, Lu; Weyand, Cornelia M.; Goronzy, Jörg J. (Frontiers in Immunology, 2020)
Healthy immune aging is in part determined by how well the sizes of naïve T cell compartments are being maintained with advancing age. Throughout adult life, replenishment largely derives from homeostatic proliferation of existing naïve and memory T cell populations. However, while the subpopulation composition of CD4 T cells is relatively stable, the CD8 T cell compartment undergoes more drastic changes with loss of naïve CD8 T cells and accumulation of effector T cells, suggesting that CD4 T cells are more resilient to resist age-associated changes. To determine the epigenetic basis for these differences in behaviors, we compared chromatin accessibility maps of CD4 and CD8 T cell subsets from young and old individuals and related the results to the expressed transcriptome. The dominant age-associated signatures resembled hallmarks of differentiation, which were more pronounced for CD8 naïve and memory than the corresponding CD4 T cell subsets, indicating that CD8 T cells are less able to keep cellular quiescence upon homeostatic proliferation. In parallel, CD8 T cells from old adults, irrespective of their differentiation state, displayed greater reduced accessibility to genes of basic cell biological function, including genes encoding ribosomal proteins. One possible mechanism is the reduced expression of the transcription factors YY1 and NRF1. Our data suggest that chromatin accessibility signatures can be identified that distinguish CD4 and CD8 T cells from old adults and that may confer the higher resilience of CD4 T cells to aging.